ANALISIS HUBUNGAN KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP MOTIVASI KERJA KARYAWAN PDAM TIRTA BENING PATI - Rochmah, Siti; Ernawati, Fidyah Yuli (JURNAL STIE SEMARANG, 2021)
The purpose of this study was to determine how much financial compensation affects Employee Work Motivation at PDAM Tirta Bening Pati and to find out how much non-financial compensation affects Employee Work Motivation at PDAM Tirta Bening Pati. Based on previous research by Ulfah (2016) and Sahari ( 2016) argues that compensation is very important. Because through compensation for employees is an effort to improve performance, passion and work motivation in employees, the hypothesis in this study is: Financial compensation affects employee work motivation at PDAM Tirta Bening Pati, non-financial compensation affects employee work motivation in PDAM Tirta Bening PatiThe population in this study were all employees of PDAM Tirta Bening Pati with a total of 190 people. The sample is 66 respondents. The test used is multiple linear regression analysis, t test, F test and the coefficient of determination. Financial compensation has a positive and significant effect on employee motivation. Non-financial compensation has a positive and significant effect on employee motivation. The work motivation of the employees of PDAM Tirta Bening Pati can be maintained or improved so that the work that is the responsibility of the employees can be carried out properly